Pengaruh Pendidikan, Pelatihan Kerja, Upah dan Kesehatan Terhadap Produktivitas Tenaga Kerja di Indonesia - Kasrina Salsabillah; Ariusni (Media Riset Ekonomi Pembangunan (MedREP), 2026)
Labor productivity is a key indicator of human capital quality and national economic competitiveness. Despite continuous socioeconomic progress in Indonesia, productivity disparities across provinces remain substantial, suggesting heterogeneous effects of human capital factors. This study examines the effects of education, job training, wages, and health on labor productivity while incorporating investment and information and communication technology (ICT) as control variables. Secondary panel data from 34 provinces during 2017–2024 were analyzed using panel data regression. The Random Effect Model (REM) was selected based on the Chow, Hausman, and Lagrange Multiplier tests. The findings reveal that job training, wages, and health have a positive and statistically significant effect on labor productivity. Education shows a positive coefficient but is not statistically significant. Investment and ICT also contribute positively as control variables. Simultaneously, all explanatory variables significantly influence labor productivity. These results highlight the importance of strengthening workforce competencies through targeted training, ensuring equitable wage policies, improving public health, and accelerating digital transformation to support sustainable productivity growth across Indonesia.